2015
DOI: 10.1007/s10661-015-4704-2
|View full text |Cite
|
Sign up to set email alerts
|

Chiral xenobiotics bioaccumulations and environmental health prospectives

Abstract: The chiral xenobiotics are very dangerous for all of us due to the different enantioselective toxicities of the enantiomers. Besides, these have different enantioselective bioaccumulations and behaviors in our body and other organisms. It is of urgent need to understand the enantioselective bioaccumulations, toxicities, and the health hazards of the chiral xenobiotics. The present article describes the classification, sources of contamination, distribution, enantioselective bioaccumulation, and the toxicities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…As a model to test toxicity after hydrocarbon removal from the liquid media and especially because some hydrocarbons remained present or are converted to more toxic forms, toxicity tests were conducted using a cucumber (C. sativus) germination seed assay [56]. Table 2 shows the percentages of germination of C. sativus seeds treated with extracts from supernatants of cultures from day 6, 15, and 21 of both fungi.…”
Section: Ecotoxicity Of the Treated Media In The Germination Of C Samentioning
confidence: 99%
“…As a model to test toxicity after hydrocarbon removal from the liquid media and especially because some hydrocarbons remained present or are converted to more toxic forms, toxicity tests were conducted using a cucumber (C. sativus) germination seed assay [56]. Table 2 shows the percentages of germination of C. sativus seeds treated with extracts from supernatants of cultures from day 6, 15, and 21 of both fungi.…”
Section: Ecotoxicity Of the Treated Media In The Germination Of C Samentioning
confidence: 99%
“…Plants have their own detoxification system with many enzymes that can metabolize organic contaminants (e.g., cytochrome P450, monooxygenases, peroxidases, glutathione S-transferases) and endophytic bacteria can live inside plants and have a potentially large impact on their metabolism (Brader et al, 2014;Sauvetre and Schröder, 2015). R-IBU has been studied to be transformed by microorganisms in biofilm reactors (Hussain et al, 2015). Chen and Rosazza (1994) reported that the reduction rate of R-IBU was twice faster than S-IBU in Nocardia.…”
Section: Biodegradabilitymentioning
confidence: 99%